The living & the dead : the rise and fall of the cult of World War II in Russia - Tumarkin, Nina (Basic Books, 1994)
World War II killed some thirty million Soviet citizens and transformed the lives of survivors and their descendants. It was the defining ordeal that shaped the history of the Soviet behemoth in the past half-century